你可能感兴趣的试题
5x3+2x 6x3+1 6x3+2x 6x2+2x
e2x(2cos3x-3sin3x) e2x(2cos3x-3sin3x)dx -6e2xsin3xdx e2x(2cos3x+3sin3x)dx
由2x﹣3=1,得2x=1﹣3 由﹣2x=1,得x=﹣2 由8﹣x=x﹣5,得﹣x﹣x=5﹣8 由2(x﹣3)=1,得2x﹣3=1
X→X.→X. X→2X→2X X→2X→X. 2X→2X→X.
由2x﹣3=1,得2x=1﹣3 由﹣2x=1,得x=﹣2 由2(x﹣3)=1,得2x﹣3=1 由8﹣x=x﹣5,得﹣x﹣x=﹣5﹣8
–2x(1-x) 2x(1-x) –2x(1+x) 2x(1+x)
y=2x2+2x+12 y=2x2-2x+12 y=2x2+2x-12 y=2x2-2x-12
3x+2x=7 3x﹣2x=﹣7 3x+2x=﹣7 3x﹣2x=7
3x2﹣5x2=﹣2x 6x2+2x2=3x2 x2+x2=2x2 ﹣2(x﹣2)=﹣2x﹣4
是奇数集,集合 是偶数集.若命题p:∀x∈A.,2x∈B.,则( ) A. ﹁p:∀x∈A.,2x∉BB. ﹁p:∀x∉A.,2x∉B ﹁p:∃x∉A.,2x∈B ﹁p:∃x∈A.,2x∉B.
是奇数集,集合 是偶数集.若命题p:∀x∈A.,2x∈B.,则( ) A.非p:∀x∈A.,2x∉BB.非p:∀x∉A.,2x∉B. 非p:∃x∉A.,2x∈B 非p:∃x∈A.,2x∉B.
y′=2xcos 2x-x2sin 2x y′=2xcos 2x-2x2sin 2x y′=x2cos 2x-2xsin 2x y′=2xcos 2x+2x2sin 2x
∀x∈R,2x2﹣1<0 ∀x∈R,2x2﹣1≤0 ∃x∈R,2x2﹣1≤0 ∃x∈R,2x2﹣1>0
c1e2x-c2e-2x+1 c1e2x+c2e-2x-1 e2x-e-2x+1 c1e2x+c2e-2x-2
e-2x+C -2e-2x -2e-2x+C 4e-2x+C
)2xn(x2+2-3x)=2xn(x-1)(x-2) ( )2xn-2(x2-3x+2)=2xn-2(x-1)(x-2) ( )2xn-2(x4+2x2-3)=2xn-2(x2+3)(x2-1)=2xn-2(x2+3)(x+1)(x-1) ( )2xn-2(x4-2x2+3)=2xn-2 (x2+3)(x2+1)
由2x﹣3(4﹣2x)=6得2x﹣12﹣2x=6 由2x﹣3(4﹣2x)=6得2x﹣12﹣6x=6
由2x﹣3(4﹣2x)=6得2x﹣12+6x=6 由2x﹣3(4﹣2x)=6得2x﹣12﹣6x=6
数据2x1,2x2,2x3的中位数为2k 数据2x1,2x2,2x3的众数为2m 数据2x1,2x2,2x3的平均数为2n 数据2x1,2x2,2x3的方差为2p